If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) = 10 + (-1) Reorder the terms: 3(-4 + x) = 10 + (-1) (-4 * 3 + x * 3) = 10 + (-1) (-12 + 3x) = 10 + (-1) -12 + 3x = 10 + -1 Combine like terms: 10 + -1 = 9 -12 + 3x = 9 Solving -12 + 3x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3x = 9 + 12 Combine like terms: -12 + 12 = 0 0 + 3x = 9 + 12 3x = 9 + 12 Combine like terms: 9 + 12 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| 2x-10x^2=0 | | .45+Y=1.0 | | 6(4m-1)+3=-99 | | 12+2x=36+x | | 3.25p+4(.75p-12)=79.25 | | x-2x=-2 | | 26=1/5n-3 | | r-7.9=-7.3 | | X^2+(2K+1)X+K=0 | | 2(10d+13)= | | 6(3z-3)-2z-15= | | 4x-9y-6x+4y= | | 4y-3x=0 | | 3n+15=-19+2n | | -3x-8y=0 | | -5x-4=-9 | | 2e+7=15 | | 10-6x-7-9x=6 | | 8n+5=20 | | 0.50+0.10(110)=0.25(116) | | 6n+2=32 | | 0.3x+17.5=x-8.12 | | 8n-5=20 | | 0=3x^2-6x+4 | | x-(4x-7)=5x-(1x+21) | | 3(x-1)=120 | | 2x-9y-5y+5y= | | 2x^2-3=-47 | | 3x+10=21 | | 6x+0.5=0 | | 10x+7+5x-12=4 | | 2(3x-1)+4=16 |